Management of hypothyroidism in general practice- A review of guidelines - Dangal, Binod (Journal of General Practice and Emergency Medicine of Nepal, 2023)
Introduction: Hypothyroidism is a common complex chronic disease and levothyroxine is considered as a standard of care in the treatment of hypothyroidism. Untreated hypothyroidism leads to devastating complications. Careful and titrated management is necessary to have optimal functioning of thyroid glands to control overall metabolism. Diagnosis: Routine evaluation with Thyroid Function Test (TFT) is recommended to diagnose Hypothyroidism, Thyroid Peroxidase (TPO) Antibody testing is done to identify autoimmune etiology and the routine need of ultrasound is determined by findings in clinical examination. Treatment: Levothyroxine is standard of treatment for hypothyroidism. Regular follow up with Thyroid Stimulating Hormone (TSH) and titrated dose of levothyroxine is recommended.